ANALISIS VARIASI HARGA BERAS DI PROVINSI RIAU DAN DAERAH PEMASOK - Desmayanti Jusar; Djaimi Bakce; Eliza Eliza (DINAMIKA PERTANIAN, 2017)
Riau is one of the provinces that is highly dependent on the supplier area, not the producer area, but the rice consumer net. This causes the price of rice to fluctuate, so the observation of rice price development is very important for the Government of Riau Province. Price fluctuations with large variations are a problem whereas price fluctuations with low variations are relatively controllable, so research on the analysis of price variations, important to do. The results show that overall rice price variation in Riau Province and supplier areas in 2006 - 2015 were is relatively stable with an increasing trend but there was a rice price jump in 2008 as a result of the global economic crisis, where food prices are rising while revenues decrease.